PENGETAHUAN IBU HAMIL TENTANG TATALAKSANA INISIASI MENYUSUI DINI - Maharani; Sri Legawati (LPPM AKPER GITA MATURA ABADI KISARAN, 2026)
Early Breastfeeding Initiation (IMD) is a group that helps new mothers start breastfeeding their babies immediately after birth, usually on the same day. This study aimed to determine community knowledge about how to initiate breastfeeding early at the Firda Hasanah Clinic in Guntung Village, Tanjung Tiram District. This research methodology uses a descriptive survey method and is cross-sectional in nature, with data. Although there were 36 respondents, the sample was determined using a sampling technique known as